Hearing "That's So Gay" and "No Homo" on Campus and Substance Use Among Sexual Minority College Students. Issue 10 (24th August 2019) - Winberg, Carter; Coleman, Todd; Woodford, Michael R.; McKie, Raymond M.; Travers, Robb; Renn, Kristen A.
ABSTRACT: Sexual orientation microaggressions are common on college campuses and can contribute to negative outcomes; yet little is known about their relationship with substance use outcomes. Among a convenience sample of cisgender sexual minority college students ( n = 574; 57.0% female, 24.9% people of color, 50.7% gay/lesbian; 72.4% public school) from 37 states (67.8% Midwest), this analysis investigates the association between hearing "that's so gay" and "no homo" on campus and hazardous alcohol use and the frequency of illicit drug use. Using multivariable regression analyses, the commonly heard phrases "that's so gay" and "no homo" were each found to significantly increase the risk for hazardous drinking and the frequency of drug use among students. Efforts should be made to create more welcoming campus climates for sexual minority students by reducing the use of these microaggressions and, in the meantime, offering supports to mitigate their harmful effects.